PEMODELAN MATEMATIKA JUMLAH PENDUDUK MINAHASA UTARA DENGAN PENDEKATAN LOGISTIK - Lubis, Anggelica; Ruata, Leli; Koesni, Artia; Pandei, Aifel; Sumampouw, Franklin A. W; Sabe, Altomi M; Mangobi, James U. L.; Maukar, Marvel (LPPM Politeknik Saint Paul Sorong, 2025)
The development of population size is a crucial factor in determining the direction of regional development. North Minahasa Regency has shown a relatively stable population growth trend each year. This study aims to construct a mathematical model using a logistic approach to predict the population of North Minahasa from 2020 to 2024. The logistic model was selected because it effectively represents growth that does not continuously increase but slows down as resources become limited. The prediction results are expected to support more accurate and sustainable development policies.